The Effect of Tax Planning, Tax Avoidance, and Earnings Management on Firm Value In Food and Beverage Companies Listed on The Indonesia Stock Exchange (IDX) - Lala Aulia Syafina; Siti Bilqis Bahirah; Acep Komara (PT. Publikasiku Academic Solution, 2024)
This study aims to determine the effect of tax planning, tax avoidance, and profit management on company value in food and beverage companies. This research uses quantitative approach method. The object of research in this study is the financial statements of manufacturing companies in the Food & Beverage industry subsector for the 2019-2023 period which are still listed on the IDX in 2023. The sample of this study was 19 companies. This research data collection technique uses documentation techniques. Data processing in this study used the Eviews application version 12. The results of this study are that tax planning has a significant effect on company value, tax avoidance does not affect on company value, profit management does not affect company value. Based on the results of data analysis in this study, tax planning significantly affects company value. Proper tax planning for a company will increase profits, minimize the tax burden to be paid, and attract the attention of investors because it guarantees the company gets maximum profits and pays maximum dividends, can increase company value. Tax avoidance does not affect on the value of the company.